Peace and conflict studies research : a qualitative perspective - Cooper, Robin, 1966-; Finley, Laura L. (Peace education., 2014)
This edited book is a new and valuable resource for students, teachers, and practitioners, providing a detailed exploration of how qualitative research can be applied in the field of peace and conflict studies. This book explores considerations and components of designing, conducting, and reporting qualitative research in this field, and also provide exemplars of recent empirical research in peace and conflict studies that employed qualitative methods. Scholars and researchers in peace and conflict studies and peace education face unique challenges in teaching, designing, and conducting qualitative research in these fields. This edited book discusses tips in designing qualitative studies in this area and for teaching emerging peace researchers best practices of qualitative inquiry. In addition, the book discusses some of the trends, challenges, and opportunities associated with research in peace and conflict studies and peace education.Written at a level appropriate for both graduate students and active researchers, the primary audience for this book is those teaching and learning about the application of qualitative methods to peace and conflict studies, as well as those conducting research in this field. There are currently approximately 230 graduate programs in peace and conflict studies. This book also provides a useful tool for researchers and students in other academic disciplines who are interested in qualitative research. Such disciplines might include education, sociology, criminology, gender studies, psychology, political science, and others.